Analisis Interaksi Guru dan Orang Tua dalam Kegiatan Sekolah Dasar - Syaima Alya Aziza; Annisa Saraswati Sanoso; Miftahul Fitriah; Fika Fitria; Anadhita Setia Pradiska; Riska Khadijah; Suhaimi Suhaimi (KAMPUS AKADEMIK PUBLISING, 2026)
Interaction between teachers and parents is an important factor in supporting students’ educational success in elementary schools. Effective collaboration between schools and families can create a supportive learning environment that contributes to students’ academic, social, and emotional development. This study aims to analyze the forms of interaction between teachers and parents in elementary school activities, the benefits obtained, the challenges encountered, and strategies to strengthen this relationship. The study employed a qualitative approach using a literature review method by analyzing several scientific journals related to teacher–parent interaction in elementary education. The results indicate that teacher–parent interaction occurs through various activities, including formal meetings, communication regarding students’ learning progress, the use of communication media, and parental involvement in school activities. These interactions provide several benefits, such as improving students’ academic achievement, learning motivation, and social–emotional development. Therefore, strengthening collaboration between teachers and parents is essential to support students’ educational success in elementary schools.